Genetic Diversity on a Rare Terrestrial Orchid, Habenaria linearifolia in South Korea: Implications for Conservation Offered by Genome-Wide Single Nucleotide Polymorphisms - Lee, Soo-Rang; Choi, Tae-Young; Jung, Su-Young (Frontiers in Plant Science, 2022)
Monitoring intraspecific diversity offers invaluable insights on conservation practices as the variation is the product of a species evolution. Accordingly, the role of population genetic diversity has drawn a great attention over the last century responding to the biodiversity loss induced by a series of anthropogenic changes. Orchids are one of the most diverse, yet ironically most rapidly disappearing plant groups due to the specialized habitat preferences. Thus, population level genetic diversity studies may offer a powerful tool for orchid conservation programs. Using 3-RAD approach, 2734 genome-wide SNPs were isolated. With the 2734 SNPs, we investigated genetic diversity and population structure on 72 individuals of H. linearifolia and H. cruciformis in Korea. Overall, the genetic diversity was well maintained in Korean Habenaria, but high FST values were estimated suggesting large population diversification with limited gene flow. Bayesian assignment analysis revealed a morphologically cryptic diversity pattern in Jeju island populations, which might serve as an evolutionarily significant unit (ESU).